MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN ASESMEN KINERJA - St Hasmiah Mustamin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
Learning outcome can be identified by evaluation to measure and evaluate students’ performance. In measuring and evaluating students’ learning outcomes, there are many types of alternative assessment that can be used, such as performance asses-ment that requires students to show their performace, either in solving problem, delivering opinion, discussing, or giving reason from their answers. Performance assesment in mathematics requires performance of a task, project, or invetigation, observation, interview, and product